Impairment of the Ability of HDL From Patients With Metabolic Syndrome but Without Diabetes Mellitus to Activate eNOS: Correction by S1P Enrichment - Denimal, Damien; Monier, Serge; Brindisi, Marie-Claude; Petit, Jean-Michel; Bouillet, Benjamin; Nguyen, Amandine; Demizieux, Laurent; Simoneau, Isabelle; Pais de Barros, Jean-Paul; Vergès, Bruno; Duvillard, Laurence (Arteriosclerosis, thrombosis, and vascular biology, 2017)
OBJECTIVE—High-density lipoprotein (HDL) from nondiabetic patients with metabolic syndrome (MetS) displays abnormalities in their lipidome, such as triglyceride enrichment and sphingosine-1-phosphate depletion. We hypothesized that these abnormalities could impair the ability of HDL to stimulate endothelial nitric oxide synthase (eNOS). APPROACH AND RESULTS—Compared with HDL from control subjects, HDL from normoglycemic patients with MetS was 39% richer in triglycerides (P<0.01) and 15% poorer in sphingosine-1-phosphate (P<0.05; n=23 in each group). eNOS activity, assessed by the conversion of L-[H]arginine to L-[H]citrulline, was 69% lower in human umbilical vein endothelial cells incubated with HDL from MetS patients than in cells incubated with HDL from controls (P<0.0001). In addition, the activating phosphorylation of eNOS at serine (Ser) 1177 and of Akt at Ser473 was 37% (P<0.001) and 39% (P<0.05) lower, respectively, with HDL from MetS patients. Sphingosine-1-phosphate enrichment of HDL from MetS patients restored their ability to stimulate eNOS activity (P<0.05), in relation with a significant increase in eNOS phosphorylation at Ser1177 (P<0.05) and in Akt phosphorylation at Ser473 (P=0.05). By contrast, triglyceride enrichment of HDL from control subjects did not modify eNOS activity (P=0.90) and phosphorylation at Ser1177 (P=0.87). CONCLUSIONS—We provide evidence that the activation of eNOS by HDL is decreased in MetS patients before the appearance of diabetes mellitus and that sphingosine-1-phosphate depletion of HDL is the main factor responsible for this defect. This has important consequences on the impairment of HDL functionality and antiatherogenic properties in these patients.